Aβ seeding potency peaks in the early stages of cerebral β‐amyloidosis. (12th July 2017) - Ye, Lan; Rasmussen, Jay; Kaeser, Stephan A; Marzesco, Anne‐Marie; Obermüller, Ulrike; Mahler, Jasmin; Schelle, Juliane; Odenthal, Jörg; Krüger, Christian; Fritschi, Sarah K; Walker, Lary C; Staufenbiel, Matthias; et al.
Abstract: Little is known about the extent to which pathogenic factors drive the development of Alzheimer's disease (AD) at different stages of the long preclinical and clinical phases. Given that the aggregation of the β‐amyloid peptide (Aβ) is an important factor in AD pathogenesis, we asked whether Aβ seeds from brain extracts of mice at different stages of amyloid deposition differ in their biological activity. Specifically, we assessed the effect of age on Aβ seeding activity in two mouse models of cerebral Aβ amyloidosis (APPPS1 and APP23) with different ages of onset and rates of progression of Aβ deposition. Brain extracts from these mice were serially diluted and inoculated into host mice. Strikingly, the seeding activity (seeding dose SD50 ) in extracts from donor mice of both models reached a plateau relatively early in the amyloidogenic process. When normalized to total brain Aβ, the resulting specific seeding activity sharply peaked at the initial phase of Aβ deposition, which in turn is characterized by a temporary several‐fold increase in the Aβ42/Aβ40 ratio. At all stages, the specific seeding activity of the APPPS1 extract was higher compared to that of APP23 brain extract, consistent with a more important contribution of Aβ42 than Aβ40 to seed activity. Our findings indicate that the Aβ seeding potency is greatest early in the pathogenic cascade and diminishes as Aβ increasingly accumulates in brain. The present results provide experimental support for directing anti‐Aβ therapeutics to the earliest stage of the pathogenic cascade, preferably before the onset of amyloid deposition. Synopsis: The highest biological seeding activity of Aβ occurs at the onset of plaque deposition. This points to the need for therapeutic targeting of Aβ at the very early stages of Alzheimer's disease. The specific seeding activity of Aβ peaks at the initial phase of Aβ deposition. The peak in Aβ seeding activity coincides with a high Aβ42/Aβ40 ratio. The overall Aβ seeding activity of brain extracts plateaus with aging. Abstract : The highest biological seeding activity of Aβ occurs at the onset of plaque deposition. This points to the need for therapeutic targeting of Aβ at the very early stages of Alzheimer's disease.